Antibacterial activity of actinomycetes isolated from different soil samples of Sheopur (A city of central India) - Hotam S Chaudhary; Jayprakash Yadav; Anju R Shrivastava; Smriti Singh; Anil K Singh; Natrajan Gopalan (Wolters Kluwer Medknow Publications, 2013)
The main objective of the present study was isolation, purification, and characterization of actinomycetes from soil samples, having antimicrobial activity against 12 selected pathogenic strains. Soils samples were taken from different niche habitats of Sheopur district, Madhya Pradesh, India. These samples were serially diluted and plated on actinomycete isolation agar media. Potential colonies were screened, purified, and stored in glycerol stock. Isolates were morphologically and biochemically characterized. These isolates were subjected to extraction for production of the antibacterial compound. Antibacterial activity and Minimum Inhibitory Concentration (MIC) of the purified extract of isolates were evaluated. Totally 31 actinomycete isolates were tested for antagonistic activity against 12 pathogenic microorganisms. Isolates AS14, AS27, and AS28 were highly active, while AS1 showed less activity against the pathogenic microorganisms. Isolate AS7 exhibited the highest antagonistic activity against Bacillus cereus (24 mm) and AS16 showed the highest activity against Enterococcus faecalis (21 mm). MIC was also determined for actinomycete isolates against all the tested microorganisms. MIC of actinomycete isolates was found to be 2.5 mg/ml against Shigella dysenteriae, Vancomycin-resistant enterococci, and Klebsiella pneumoniae, and was 1.25 mg/ml for Staphylococcus saprophyticus, Streptococcus pyogenes, Staphylococcus epidermidis, Methicillin-resistant Staphylococcus, Bacillus cereus, Staphylococcus xylosus, Methicillin-resistant Staphylococcus aureus, Enterococcus faecalis, and Staphylococcus aureus. All actinomycetes isolates showed antibacterial activity against S. aureus, while they showed less activity against S. dysenteriae. These isolates had antibacterial activity and could be used in the development of new antibiotics for pharmaceutical or agricultural purposes.